2020
DOI: 10.2217/fon-2020-0039
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Outcomes of Radium-223 Dichloride for Metastatic Castration Resistant Prostate Cancer

Abstract: Aim: Timing of radium-223 (Ra-223) in metastatic castration-resistant prostate cancer (mCRPC) remains challenging due to alternative options and short window of opportunity. Methods: Ra-223 treated patients in the CAPRI-registry were included. Outcomes were evaluated based on treatment line of Ra-223. Results: Out of 285 patients, 49% received Ra-223 in line ≥3. 51% completed six Ra-223 injections and 34% had a symptomatic skeletal event after first Ra-223 without differences between subgroups. After correctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…This label change has impact on the treatment arsenal of metastatic CRPC patients. Due to the development of visceral metastases, impaired performance status and reduced hematological function in later disease stages, the window of opportunity to receive radium-223 therapy might be missed [ 4 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This label change has impact on the treatment arsenal of metastatic CRPC patients. Due to the development of visceral metastases, impaired performance status and reduced hematological function in later disease stages, the window of opportunity to receive radium-223 therapy might be missed [ 4 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in 2018 the European Medicine Agency (EMA) restricted the use of [ 223 Ra]RaCl 2 to patients with more than six osteoblastic lesions progressing to at least two systemic therapies for mCRPC or ineligible for any systemic mCRPC treatment [ 10 ]. The consequent delay of [ 223 Ra]RaCl 2 administration in the later phases of the disease might negatively affect OS, making the patient’s selection process even further challenging [ 11 ]. In this scenario, identifying prognostic factors potentially able to select patients most likely to benefit from [ 223 Ra]RaCl 2 since baseline has become a crucial issue.…”
Section: Introductionmentioning
confidence: 99%
“…These results also indicate that radium-223, as appropriate, could be considered as one of the early treatment options integrated into the management of patients with mCRPC, with no apparent adverse impact on long-term prognosis. Other real-world studies have shown correlations between overall survival and completion of 5 or 6 radium-223 injections, use of radium-223 in the first or second line, or use before chemotherapy [11][12][13][14][15][16][17][18]. Patients able to complete the full course of radium-223 injections are likely to have fewer symptoms (including less pain), less disease burden, a good performance status, low baseline PSA and ALP levels, and high baseline hemoglobin levels [11,[19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%